KEAMANAN DATA PEMILU DI ERA CYBERCRIME: ANALISIS KASUS PERETASAN SITUS KOMISI PEMILIHAN UMUM - Andrianika, Siska; Yudisthira, Muhammad Syahrul; Waty, Reni Rentika (Bawaslu Provinsi Jawa Barat, 2023)
This research explores cybercrime incidents which resulted in data leaks on the official website of the General Election Commission (KPU). This happened repeatedly from 2004 to 2023. So, this research aims to determine the causes and impacts of cybercrime related to election data leaks on the official KPU website, as well as formulating strategic recommendations to strengthen election data security. Information security risk theory, policy decisions, and the concept of political trust are used to analyze phenomena and data with a qualitative method approach. The research results show that the KPU data leak occurred because the data security system that had not been built was not strong enough. Hacking cases have repeatedly led to a decrease in political trust and delegitimization of the election implementation process, so that the KPU requires cooperation from various stakeholders to create a safe and credible data system.